Nutritional disorders - Howeler, Reinhardt H. (International Center for Tropical Agriculture, 1980)
Different nutritional deficiencies or toxicities may limit bean development and yield. N and P deficiencies are the most frequent, although deficiency of minor elements and Al/Mn toxicity can reduce yields considerably. Nutritional problems are usually diagnosed by soil and plant tissue analyses and the observation of symptoms produced by nutritional disorders. Optimum pH for bean production varies between 6.5-7.5; within these limits, the majority of the plant nutrients have their max availability. Color illustrations are given of the symptoms of plant deficiencies and toxicities. (CIAT)